Pemberdayaan Pengajian Dib’aiyah di Kalangan Remaja Yayasan Pondok Pesantren Nganjuk - Makhmudah , Siti (Rahmah : Jurnal Pengabdian Masyarakat, 2025)
The purpose of the empowerment activity of the Al Barzanji Dib'aiyah study group as a forum to develop spiritual, emotional, intellectual qualities and the establishment of ukwah between teenagers of the An Nur Foundation in Prambaon Nganjuk, which is manifested in the cultivation of religious adolescent characters. This service uses the ABCD research method. The results of this service activity found a solution with a persuasive approach with the community and teenagers around Prambon so as to foster a spirit of cooperation to motivate in mentoring and directing, habituation, routine implementation of the Al Barzanji Dib'aiyah study group with mutual agreement